Evaluation of Flood Impact of Waterway Project Based on One-Dimensional Hydrodynamic Model ——A Case Study of 2000-ton Laibin-Guiping Waterway Project of Datengxia Gorge - XIE Tianyun; WEI Lusi; LI Yi; ZHOU Shunxuan; LIN Xinyi (Renmin Zhujiang)
A one-dimensional hydrodynamic model is used to accurately and systematically evaluate the flood impact of the 2000-ton waterway project with a total length of 193.876 km from Laibin to Guiping.The model is calibrated and validated,and the changes in the water level of the channel are observed.On this basis,this study analyzes and evaluates the impact of waterway regulation and construction on the channel flood discharge,hydrological station observation,bridge operation,water intake,and other aspects.The results show that the project implementation leads to a drop in the water level in the project section,which has an adverse effect on the water level observation scheme of the hydrological station.Hence,it is necessary to take corresponding remedial measures such as supplementary monitoring.Moreover,the result indicates that it has no adverse impact on bridges,water intakes,flood discharge and drainage,and irrigation.The assessment results can provide a rich and detailed basis for the approval and management of the water administration department.